PROPOSAL PENDEKATAN INTERKULTURAL KEPADA SUKU BOTI TENTANG KONSEP KEILAHIAN UIS NENO - Yesri Esau Talan; Tony Salurante (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The intercultural approach is effective in its application in the context of the Boti tribe because this tribe is exclusive and considers the Bible as a foreign culture that threatens the halaika culture. The exclusive attitude of the Boti tribe is carried out on the basis of maintaining the halaika culture so that it does not experience assimilation and is eroded with the times. The intercultural approach is a biblical missionary approach. This approach uses the Boti tribal concept of uis neno as a medium to communicate about God. The method used in this study is a qualitative research, the data obtained through interviews, documentation and observations are described with other reference sources related to this research. The results obtained in this study are, the intercultural approach is a biblical missional approach and its application is persuasive in the context of the Boti tribe. The culture they understand and practice is used as a medium of gospel communication.